Skeletal muscle oxygenation during cycling at different power output and cadence. Issue 3 (7th February 2019) - Shastri, Lisha; Alkhalil, Mariana; Forbes, Claire; El‐Wadi, Tina; Rafferty, Gerrard; Ishida, Koji; Formenti, Federico
Abstract: The selection of cadence during cycling may be determined by a number of factors, including the degree of oxygenation in the exercising skeletal muscle. The purpose of this study was to determine the degree of muscle oxygenation associated with different cycling cadences and exercise intensities, and its putative role in the choice of self‐selected cadence during cycling. We recorded cardiopulmonary and metabolic responses to cycling at exercise intensities of 70% and 90% of the ventilatory threshold ( T vent ), and used near‐infrared spectroscopy to determine tissue saturation index as a measure of skeletal muscle ( vastus lateralis ) oxygenation. Twelve participants cycled at cadences of 30, 50, 70, 90, and 110 revolutions per minute (rpm), each for 4 min, in a randomized sequence, interspersed with active recovery periods. Despite cardiopulmonary and metabolic responses being greater at 90% than at 70% T vent, and at 110 rpm compared with lower cadences, vastus lateralis oxygenation was not different between the two exercise intensities and five cadences tested. Our results indicate that skeletal muscle tissue saturation index is not substantially affected during cycling for short periods of time at constant, moderate exercise intensity at cadences between 30 and 110 rpm, suggesting that skeletal muscle oxygenation may not be an important negative feedback signal in the choice of self‐selected cadence during cycling at moderate exercise intensity. Abstract : Skeletal muscle oxygenation measured in the vastus lateralis with near‐infrared spectroscopy at high frequency (10 Hz) did not vary during cycling exercise between cadences of 30 and 110 revolutions per minute at two levels of moderate exercise intensity in a group of 12 participants.